De Hollywood a Aracaju: a Segunda Guerra Mundial por intermédio dos cinemas (1939-1945) - Cruz, Andreza Santos [UNESP] (2013)
The World War II was the most intense military conflict occurred in the Twentieth Century. And the War quickly became an interesting topic for film production. Considering the large amount of Hollywood movies that circulated in Brazil at that time, this thesis analyses how North American movies, exhibited between 1939 and 1945 in Aracaju, had influenced in a creation of common sense about World War II. People who lived in Aracaju had seen closely the consequences of Brazilian ships sinked, in August 1942. And, in September, Aracaju's movie theaters started the exhibition of “Anti-nazi” movies. After to examine the reception of movies was clear the Brazilian state's effort to control all mass media (through the Department of Press and Propaganda and their representation in Sergipe), as well as they had tried to get the spectator attention to particular aspects in foreign productions. In this search some documents were analyzed based on the New Cultural History as newspapers and magazines, especially those that circulated in Aracaju containing advertisements and comments about the premieres of films, as well as official documents, the movies and others sources. Therefore the research results indicate a particular way in going to the movies in Aracaju, as the influence exerted by Hollywood movies, mostly those that mention the World War II and Brazil enemies, in moviegoers of cinemas Rio Branco, Rex, Guarany, São Francisco and Vitória